In-vitro activity of polymyxin B in combination with imipenem, rifampicin and azithromycin versus multidrug resistant strains of Acinetobacter baumannii producing OXA-23 carbapenemases - Bean David C; Wareham David W (BMC, 2006)
Abstract Background Acinetobacter baumannii has emerged as a major nosocomial pathogen worldwide. Many of the circulating strains exhibit multi-drug resistance remaining consistently susceptible only to polymyxins. In-vitro studies have reported that polymyxins combined with carbapenems, rifampicin or azithromycin are synergistic against these strains despite in-vitro resistance to these agents alone. The use of antimicrobial combinations have therefore been advocated for the treatment of severe A. baumannii infection in man. In order to determine whether such combinations are synergistic against the prevalent clones of multi-drug resistant A. baumannii causing infection in the UK, we performed synergy testing against representative isolates using two rapid Etest methods. Methods The activity of polymyxin in combination with imipenem, azithromycin or rifampicin was assessed against five strains of multi-drug resistant A. baumannii encoding OXA-23 carbapenemases. Synergy studies were performed by Etest-agar dilution and a combined Etest strip method. Synergy was defined as a FICI of ≤ 0.5. Results All strains were resistant to β-lactams, carbapenems, quinolones and aminoglycosides but susceptible to polymyxins. Marked synergy was not seen with polymyxin in combination with imipenem, rifampicin or azithromycin against any of the strains. Borderline synergy (FICI = 0.5) was seen against one strain belonging to OXA-23 clonal group 2, using the Etest-agar dilution method only. Conclusion In-vitro synergy with polymxyin in combination with imipenem, rifampicin or azithromycin is highly strain and method dependent. As reliable synergy could not be demonstrated against the prevalent UK multi-drug resistant strains, use of such combinations should not be used for empirical treatment of these infections in the UK. The optimal treatment for serious multi-drug A. baumannii infection and the role of combination therapy should be addressed in a prospective clinical trial.